1997
DOI: 10.1016/s0029-7844(96)00478-4
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic determinants of abruptio placentae

Abstract: Severe fetal growth restriction, prolonged rupture of membranes, chorioamnionitis, hypertension (before pregnancy and pregnancy-induced), cigarette smoking, advanced maternal age, unmarried status, and male fetal gender are significant etiologic determinants of placental abruption. Non-SGA determinants appear to operate largely independently of their effects on fetal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
111
4
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 23 publications
24
111
4
2
Order By: Relevance
“…9 Regarding factors previously known to be related to placental abruption, our findings of a 3-fold increased risk of placental abruption in pregnancies with IUGR fetuses is in a similar range as Kramer and co-workers. However, they subdivided their results into women with 4 fetuses between mild IUGR < -15% and > -25% (OR = 1.3) and severe IUGR < -25% (OR = 4.0).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Regarding factors previously known to be related to placental abruption, our findings of a 3-fold increased risk of placental abruption in pregnancies with IUGR fetuses is in a similar range as Kramer and co-workers. However, they subdivided their results into women with 4 fetuses between mild IUGR < -15% and > -25% (OR = 1.3) and severe IUGR < -25% (OR = 4.0).…”
Section: Discussionmentioning
confidence: 99%
“…One strength of this study is that most previously known risk factors for placental abruption were of similar size, as reported earlier. The routine dating of 4 pregnancy by ultrasound at 18 to 20 weeks of gestation, used here in the definition of IUGR and fetal loss, would represent another strength. In addition, ours is a fairly large study, including both personal interviews and an examination of medical records.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature separation of the placenta occurs in only 1 % of all pregnancies, yet it is an important cause of stillbirth, preterm delivery, early neonatal death and even maternal death 1 . Placental abruptio accounts for 20 % to 25 % of antepartum hemorrhages.…”
Section: Introductionmentioning
confidence: 99%
“…In our study premature rupture of membranes was found in 14.44 % cases. Pregnancy induced hypertension is a major risk factor for abruptio placentae [12] . In our series, 38.89 % cases had pregnancy induced hypertension.…”
Section: Discussionmentioning
confidence: 99%